The link between detail generation and eye movements when encoding and retrieving complex images. Issue 10 (25th November 2020) - Lalla, Azara; Agostino, Caterina; Sheldon, Signy
ABSTRACT: Examining eye movement patterns when encoding and retrieving visually complex memories is useful to understand the link between visuo-perceptual processes and how associated details are represented within these memories. Here, we used images of real-world scenes (e.g., a couple grocery shopping) to examine how encoding and retrieval eye movements are linked to the details used to describe complex images during these two phases of memory. Given that memories are often elaborated upon during retrieval, we also examined whether eye-movements at retrieval related to details that were the same as those described when encoding the image (reinstated details) as well as details about the image event that were not initially described at encoding (newly generated details). Testing young healthy participants, we found that retrieval eye movements, specifically eye fixation rate, predicted reinstated details, but not newly generated details. This suggests that visuo-perceptual processes are preferentially engaged at retrieval to reactivate perceived information. At encoding, we found a relationship between eye movements and detail generation that changed over time. This relationship was positive early on in the encoding phase but changed to a negative relationship later in the phase, indicating that a unique relationship exists between activating visuo-perceptual processes during early encoding versus late encoding. Overall, our results provide new insights into how visuo-perceptual processes contribute to different components of complex memory.